Engineering Oxygen‐Irrelevant Radical Nanogenerator for Hypoxia‐Independent Magnetothermodynamic Tumor Nanotherapy. Issue 4 (18th January 2021) - Shen, Yujia; Dong, Caihong; Xiang, Huijing; Li, Cuixian; Zhuang, Fan; Chen, Yixin; Lu, Qing; Chen, Yu; Huang, Beijian
Abstract: Tumor hypoxia substantially lowers the treatment efficacy of oxygen‐relevant therapeutic modalities because the production of reactive oxygen species in oxygen‐relevant anticancer modalities is highly dependent on oxygen level in tumor tissues. Here a distinctive magnetothermodynamic anticancer strategy is developed that takes the advantage of oxygen‐irrelevant free radicals produced from magnetothermal decomposable initiators for inducing cancer‐cell apoptosis in vitro and tumor suppression in vivo. Free‐radical nanogenerator is constructed through in situ engineering of a mesoporous silica coating on the surface of superparamagnetic Mn and Co‐doped nanoparticles (MnFe2 O4 @CoFe2 O4, denoted as Mag) toward multifunctionality, where mesoporous structure provides reservoirs for efficient loading of initiators and the Mag core serves as in situ heat source under alternating magnetic field (AMF) actuation. Upon exposure to an exogenous AMF, the magnetic hyperthermia effect of superparamagnetic core lead to the rapid decomposition of the loaded/delivered initiators (AIPH) to produce oxygen‐irrelevant free radicals. Both the magnetothermal effect and generation of toxic free radicals under AMF actuation are synergistically effective in promoting cancer‐cell death and tumor suppression in the hypoxic tumor microenvironment. The prominent therapeutic efficacy of this radical nanogenerator represents an intriguing paradigm of oxygen‐irrelevant nanoplatform for AMF‐initiated synergistic cancer treatment. Abstract : The conceptual advance of this work is the proposed and developed magnetothermodynamic tumor nanotherapy based on the elaborately engineered Mag@MSNs@AIPH nanomedicines, which act as oxygen‐irrelevant radical nanogenerator for augmenting the nanotherapeutic efficacy of magnetic tumor hyperthermia and oxygen‐irrelevant free radical‐based tumor‐oxidative nanotherapy.